Spontaneous mirror-symmetry breaking coupled to top-bottom chirality transfer: from porphyrin self-assembly to scalemic Diels–Alder adducts. Issue 81 (25th September 2019) - Arlegui, Aitor; Soler, Bernat; Galindo, Alex; Arteaga, Oriol; Canillas, Adolf; Ribó, Josep M.; El-Hachemi, Zoubir; Crusats, Joaquim; Moyano, Albert
Abstract : This report shows how the net supramolecular chirality that emerged by spontaneous mirror-symmetry breaking (SMSB) at the mesoscale level can be transferred towards asymmetric solution chemistry. Abstract : This report shows how the net supramolecular chirality that emerged by spontaneous mirror-symmetry breaking (SMSB) at the mesoscale level can be transferred towards asymmetric solution chemistry. The J-aggregates obtained by self-assembly of an achiral porphyrin act as chiral counteranions in an iminium-promoted Diels–Alder reaction, leading to enantiomeric imbalances in the final adducts.